Adhesion Molecule Polymorphisms and Pulse Wave Velocity in American Youth - Zhu, Haidong (2008)
BACKGROUND: Our research group recently reported that aorto-radial (radial) and aorto-dorsalis-pedis (foot) pulse wave velocity (PWV) as proxies of arterial stiffness are substantially heritable in healthy youth. This paper aimed at uncovering the genetic contributions of adhesion molecules, key members in the inflammatory process, to PWV in these young individuals. METHODS: Radial and foot PWV were non-invasively measured with applanation tonometry in 702 black and white subjects (42% blacks, mean age 17.7 ±3.3 years) from the Georgia Cardiovascular Twin Study. Eight functional polymorphisms from genes for E-selectin (SELE), P-selectin (SELP), intercellular adhesion molecules-1 (ICAM1), and vascular cell adhesion molecules-1 (VCAM1) were genotyped. RESULTS: Youth with Ser290Asn or Asn290Asn genotype (SELP) compared to those with Ser290Ser had an increase in both radial and foot PWV (6.61±0.07 vs. 6.41±0.05 m/s, p=0.026; 7.22±0.05 vs. 7.04±0.04 m/s, p=0.007). TT homozygotes of rs2244529 (SELP) had higher foot PWV (7.28±0.07 vs. 7.06±0.03 m/s, p=0.002) than CT heterozygotes and CC homozygotes. There appeared to be a decrease in foot PWV in youth with the 241Arg allele (ICAM1) as compared to those without (6.96±0.08 vs. 7.14±0.03 m/s, p=0.005). For the Asp693Asp (C to T) polymorphism (VCAM1), CC genotype had higher foot PWV than CT and TT genotypes (7.18±0.04 vs. 6.95±0.06 m/s, p<0.0001). There was an epistatic interaction between Ser290Asn, Gly241Arg, and Asp693Asp on foot PWV (p=0.017), explaining 3.6% variance of the foot PWV. CONCLUSION: Genetic variation of adhesion molecules may be implicated in the development of arterial stiffness. Screening for adhesion molecule polymorphisms may help identify high-risk youth.